Motivation in the Sunnah of the Prophet, the desire and awe of its types and signs of mercy to the nation - Mohd Sobali, A. (Universiti Sains Islam Malaysia, 2024)
The religion of Islam, which was brought by the Prophet Muhammad, is a mercy to the world. This compassion embraces every creatures, human or animal. The mission led by Muhammad bin Abdullah, was regarded as the Prophet of mercy, who preached the message, guide the needs of human and illuminate people out of the darkness of polytheism and disbelief to the light guide and peace. One of the important aspect that was conveyed by the Prophet is his inspiring motivational technique in which encourages people and stimulates them to produce good deeds for the development of human capital and Islamic civilisation. It is beyond doubt that the Prophet’s motivational skill is quite unique, different from the others’. His method is not only a carrot and stick, it is a heartening technique, and motivating human to spread mercy in this world but also in the life of hereafter. Thus, this article aims to explore the Prophet’s motivational endeavour, its types and signs of his mercy to the people. The present study employed qualitative approach in which textual analysis is regarded as its main apparatus of scrutiny. The study in its finding extracts exceptional techniques applied by the Prophet in motivating people to spread mercy to the world.